READING PROFILE OF EFL UNDERGRADUATE STUDENTS:(A Case Studyof Eighth Semester Studentsof English Education Programin a Private Collegein Subang ) - Maulida, Ferany Shaily (2015)
This study reports EFL undergraduate students'reading profile and its relation to their reading performance. Students' reading profile here are associated to the reading activity which covers of reading habits, reading preferences, reading interest as well as their reading attitude. Taking place in one private college, this study employed qualitative approach. Questionnaire, interview and Likert-scale ASRA (Adult Survey of Reading Attitude) were used as primary technique for data collection. In addition, selected relevant information pieces from GPA and reading score were also used to complement the data from the primary sources. Data from questionnaire and interview were transcribed and categorized to find students' reading profile. The major conclusion of the study reveals that most of them are indicated not to have good English reading habits although they had positive attitude toward reading. This is proved by the fact that they do not always read English everyday which means that reading English practices is not their habitual activity. The reasons for not having regular English reading practices are that they do not understand the content of the text in English and encounter a lot of unfamiliar words that obstruct reading comprehension. It also reveals that their reading performance is low and thus their positive reading attitude do not reflect in their reading performance.